The Impact of the Wafa Method in Tahfidzul Qur'an on Student Motivation and Learning Interest - Aripin, Moh.; Nasution, Khoiruddin; Teguh, Mufrod; Umwari, Yvette (At-Tarbiyat, 2025)
This study aims to evaluate the impact of implementing the Wafa Method in Tahfidzul Qur'an education on student motivation and learning interest at SDIT Az Zahra, SDIT Darul Hikmah, and SDIT Luqman Al Hakim in Sragen for the 2023/2024 academic year. The research is driven by three primary objectives: (1) to analyze the effect of the Wafa Method implementation on student motivation, (2) to assess its impact on student learning interest, and (3) to explore how the development of this method influences overall improvements in both motivation and learning interest. Employing a field research methodology, this study utilizes parametric analysis techniques to evaluate the relationships between variables. The research population comprises 214 sixth-grade students, including 140 from SDIT Az Zahra, 30 from SDIT Darul Hikmah, and 44 from SDIT Luqman Al Hakim. A sample of 25% of the population, totaling 54 students, was selected for the study. Data collection involved interviews and structured questionnaires. The analysis reveals three key findings: (1) The implementation of the Wafa Method significantly enhances student motivation across all three schools, with a higher degree of method application correlating with increased motivation. (2) Similarly, the method shows a substantial positive effect on student learning interest, with intensified usage leading to greater interest. (3) Overall, the application of the Wafa Method contributes positively to the development of student motivation and interest, demonstrating a direct correlation between the extent of method application and the improvement in both aspects. The study concludes that integrating the Wafa Method into Tahfidzul Qur'an education can effectively boost student motivation and learning interest at SDIT Az Zahra, SDIT Darul Hikmah, and SDIT Luqman Al Hakim.